Domain-Dependent Evolution Explains Functional Homology of Protostome and Deuterostome Complement C3-Like Proteins - Peng, Maoxiao; Li, Zhi; Cardoso, João C. R.; Niu, Donghong; Liu, Xiaojun; Dong, Zhiguo; Li, Jiale; Power, Deborah M. (Frontiers in Immunology, 2022)
Complement proteins emerged early in evolution but outside the vertebrate clade they are poorly characterized. An evolutionary model of C3 family members revealed that in contrast to vertebrates the evolutionary trajectory of C3-like genes in cnidarian, protostomes and invertebrate deuterostomes was highly divergent due to independent lineage and species-specific duplications. The deduced C3-like and vertebrate C3, C4 and C5 proteins had low sequence conservation, but extraordinarily high structural conservation and 2-chain and 3-chain protein isoforms repeatedly emerged. Functional characterization of three C3-like isoforms in a bivalve representative revealed that in common with vertebrates complement proteins they were cleaved into two subunits, b and a, and the latter regulated inflammation-related genes, chemotaxis and phagocytosis. Changes within the thioester bond cleavage sites and the a-subunit protein (ANATO domain) explained the functional differentiation of bivalve C3-like. The emergence of domain-related functions early during evolution explains the overlapping functions of bivalve C3-like and vertebrate C3, C4 and C5, despite low sequence conservation and indicates that evolutionary pressure acted to conserve protein domain organization rather than the primary sequence.